PARP1 Regulates the Biogenesis and Activity of Telomerase Complex Through Modification of H/ACA-Proteins - Savelyev, Nikita V.; Shepelev, Nikita M.; Lavrik, Olga I.; Rubtsova, Maria P.; Dontsova, Olga A. (Frontiers in Cell and Developmental Biology, 2021)
Poly(ADP-ribose) polymerase 1 (PARP1) is established as a key regulator of the cellular DNA damage response and apoptosis. In addition, PARP1 participates in the global regulation of DNA repair, transcription, telomere maintenance, and inflammation response by modulating various DNA-protein and protein-protein interactions. Recently, it was reported that PARP1 also influences splicing and ribosomal RNA biogenesis. The H/ACA ribonucleoprotein complex is involved in a variety of cellular processes such as RNA maturation. It contains non-coding RNAs with specific H/ACA domains and four proteins: dyskerin (DKC1), GAR1, NHP2, and NOP10. Two of these proteins, DKC1 and GAR1, are targets of poly(ADP-ribosyl)ation catalyzed by PARP1. The H/ACA RNA-binding proteins are involved in the regulation of maturation and activity of the telomerase complex, which maintains telomere length. In this study, we demonstrated that of poly(ADP-ribosyl)ation influences on RNA-binding properties of DKC1 and GAR1 and telomerase assembly and activity. Our data provide the evidence that poly(ADP-ribosyl)ation regulates telomerase complex assembly and activity, in turn regulating telomere length that may be useful for design and development of anticancer therapeutic approaches that are based on the inhibition of PARP1 and telomerase activities.